Salmonella Sepsis presenting as Early Onset Neonatal Sepsis - Shrestha, Nipun; Shrestha, Dhruba (Journal of Nepal Paediatric Society, 2018)
Neonatal sepsis is one of the feared cause of neonatal death in both term and preterm infants, leading up to 30% of neonatal death in developing countries. Salmonella sepsis is one of the uncommon causes of early onset neonatal sepsis. Here we present a case of early onset neonatal sepsis due to Salmonella species. Baby was delivered vaginally with good Apgar score. Within few hours of birth, baby developed respiratory distress and was admitted with empirical antibiotics. The blood culture showed the growth of Salmonella species. Child was treated with IV antibiotics and responded well to it and was discharged home without complication.